PERBEDAAN TURNOVER INTENTION ANTARA GENERASI X DAN Y DI RUMAH SAKIT UMUM X DI MEDAN - Sri Ramadhani; Laksana Tobing; Siska Dwi Ningsih; Yunarto Dakhi (JURNAL PSYCHOMUTIARA, 2020)
Human resources are an important factor in a company. Discharge of employees from a company will have a considerable impact. Employee turnover has always been a major problem faced by organizations without considering location, size, nature of the business, and business strategy. The high level of employee turnover can be seen from how much desire to move owned by employees in a company. This study aims to determine the effect of Generation X and Y on turnover intention on permanent employees of the General Hospital X in Medan. This study involved 23 employees of Medan X General Hospital with a minimum service period of 1 year. Data obtained through two scales, namely the scale of Generation X and Y and turnover intention scale. The results of the regression analysis showed that Generation X and Y had a positive and significant effect on turnover intention in Medan X General Hospital employees. Generation X and Y are among the predictors of turnover intention. The results of the regression analysis showed that Generation X and Y had a positive and significant effect on turnover intention in Medan X General Hospital employees. Generation X and Y become one of the predictors of turnover intention with a contribution of 12.9%. The implication of this research is expected to the company to pass the evaluation and approach to employees that they (employees) are needed to work in the company, employees need to be given support in working in the company in the form of opportunities to experience increased self-potential development, fulfillment of needs in accordance with work , training to foster or expel and develop creativity at work, equipping superiors with the ability to guide (mentoring), skills for personal relationships and effective ability in problem solving, good decision making, communication and negotiations that do not harm the rights or the individual (employees ).